2022
DOI: 10.3389/fpubh.2022.837504
|View full text |Cite
|
Sign up to set email alerts
|

Serving the Vulnerable: The World Health Organization's Scaled Support to Countries During the First Year of the COVID-19 Pandemic

Abstract: The Inter-Agency Standing Committee (IASC), created by the United Nations (UN) General Assembly in 1991, serves as the global humanitarian coordination forum of the UN s system. The IASC brings 18 agencies together, including the World Health Organization (WHO), for humanitarian preparedness and response policies and action. Early in the COVID-19 pandemic, the IASC recognized the importance of providing intensified support to countries with conflict, humanitarian, or complex emergencies due to their weak healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Most of these recommendations have already been put in place by the International Health Regulations (2005) agreement of the World Health Organization (WHO, 2021), yet reviews found that many countries do not fully meet pandemic preparedness requirements. Consequently, recent recommendations included increasing the authority and funding of the WHO (Duff et al, 2021; Independent Panel for Pandemic Preparedness and Response, 2021), and the participation of countries in the efforts of WHO and United Nations since these organizations coordinate responses to humanitarian crises, and to pandemics specifically (Bajard et al, 2022; Brown & Susskind, 2020). Finally, because of increasing evidence that links environmental and climate change to emerging infectious diseases with pandemic potential (i.e., changes in patterns of human–nonhuman animal interactions giving way to zoonotic spillover of pathogens; C.…”
Section: Global Identity and Cooperationmentioning
confidence: 99%
“…Most of these recommendations have already been put in place by the International Health Regulations (2005) agreement of the World Health Organization (WHO, 2021), yet reviews found that many countries do not fully meet pandemic preparedness requirements. Consequently, recent recommendations included increasing the authority and funding of the WHO (Duff et al, 2021; Independent Panel for Pandemic Preparedness and Response, 2021), and the participation of countries in the efforts of WHO and United Nations since these organizations coordinate responses to humanitarian crises, and to pandemics specifically (Bajard et al, 2022; Brown & Susskind, 2020). Finally, because of increasing evidence that links environmental and climate change to emerging infectious diseases with pandemic potential (i.e., changes in patterns of human–nonhuman animal interactions giving way to zoonotic spillover of pathogens; C.…”
Section: Global Identity and Cooperationmentioning
confidence: 99%
“…At the country level, the minimum requirements for delivery of these COVID-19 tools was mapped in four of six WHO regions and 105 countries surveyed to identify potential bottlenecks and capacity gaps to inform planning and deployment (35). In 2020, WHO procured and supplied critical COVID-19 health commodities for 167 (86%) of its Member States (29), which included 16 thousand oxygen concentrators, 40 thousand oxygen monitors (5) as well as 200 million masks and millions more personal protective equipment (36) and by February 24, 2021, COVAX, the vaccines pillar of the ACT Accelerator commenced deployment of COVID-19 vaccines to participating economies (37).…”
Section: Technical Assistance and Service Deliverymentioning
confidence: 99%